Perinatal Outcomes of Pregnant Women with Cardiac Disease at the “Ramón Gonzalez Coro” Gynecologic & Obstetric Teaching Hospital. - Yanara Gutiérrez Aliaga; Ileana Chio Naranjo; Elena Guerra Chang; Viviana de la Caridad Sáez Cantero (Medisur)
Introduction: pregnancy in women with heart disease is commonly associated with increased perinatal morbidity. Objective: to describe perinatal outcomes in pregnant women with heart disease who were treated according to a new working protocol. Method: a descriptive study with some analytic aspects was conducted in the Heart Disease and Pregnancy service of the “Ramón Gonzalez Coro’’ Gynecologic and Obstetric Teaching Hospital from 2000-2009. The universe consisted on the 472 pregnant women with heart disease that received follow up during that period. They were treated according to the protocol applied since 2000. Data were obtained through a questionnaire and were processed using the SPSS 11,5 system for Windows, through determination of absolute and relative frequencies. They included: obstetric complications, mode of delivery, cesarean indication, gestational age at delivery and neonatal complications. Results: 51 (10, 8 %) patients presented obstetric complications. Vaginal delivery was the most common mode of pregnancy termination. It took place in 242 (51, 3 %) patients. Cesarean sections were performed in 146 (30, 9 %) of cases, being previous cesarean sections the first cause, 42 (28, 8 %). 17 (3, 6 %) patients presented neonatal complications. Conclusion: the new protocol applied to pregnant women with heart disease at ‘’Ramón Gonzalez Coro’’ Gynecologic and Obstetric Teaching Hospital, contributed to improve perinatal outcomes.